(untitled) (Huellas, 2025)
Within the different logics of production in a city (market, state, social needs) the following work aims at analyzing how these logics are linked, based on the spatiality arising from the collective action and self-management strategies of the civil association “Mujeres sin techo” (Homeless women) to have a fair access to habitat in the city of Tandil. The aim is to make it visible how these forms of territorializing collective action through the social production of habitat arise from the logics of social needs; but in certain moments, contexts or structures they manage to generate points of encounter or dialogue with both the logic of the state and the market in the production of urban space.